Molecular mechanisms of polymyxin resistance and detection of mcr genes - Mlynarcik, Patrik; Kolar, Milan (Biomedical papers, 2019)
Antibiotic resistance is an ever-increasing global problem. Major commercial antibiotics often fail to fight common bacteria, and some pathogens have become multi-resistant. Polymyxins are potent bactericidal antibiotics against gram-negative bacteria. Known resistance to polymyxin includes intrinsic, mutational and adaptive mechanisms, with the recently described horizontally acquired resistance mechanisms. In this review, we present several strategies for bacteria to develop enhanced resistance to polymyxins, focusing on changes in the outer membrane, efflux and other resistance determinants. Better understanding of the genes involved in polymyxin resistance may pave the way for the development of new and effective antimicrobial agents. We also report novel in silico tested primers for PCR assay that may be able distinguish colistin-resistant isolates carrying the plasmid-encoded mcr genes and will assist in combating the spread of colistin resistance in bacteria.
Keywords: polymyxin; colistin; resistance; LPS